1992
DOI: 10.1111/j.1365-2249.1992.tb05876.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene frequency and partial protein characterization of an allelic variant of mannan binding protein associated with low serum concentrations

Abstract: SUMMARYLow plasma concentration of mannan binding protein (MBP) has been shown to be the basis for a common opsonic deficiency and suggested to be caused by a single nucleotide substitution at base 230 of exon 1 in the MBP gene. This substitution causes a replacement of glycine (eodon GGC) with aspartic acid (codon GAC). Of 123 healthy Danish individuals investigated by polymerase chain reaction performed on exon 1, followed by restriction fragment length polymorphism or allospecific probing, 93 were homozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
9

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(67 citation statements)
references
References 14 publications
2
55
1
9
Order By: Relevance
“…encoded in exon 1 ofihe MBP gene; 64 were homozygous Ibr Ihc GGC allele (71 9"/,,); 21 were heterozygous for the GAC allcle (23-5%); and four were homozygous for the GAC allele (4 5%), respectively (Table I), This gives a frequency ofthe GAC allele of 0-16. which is nol significantly differenl from that of healthy Danish controls (0-13) (/*-0-65) [20] (Fig. 3).…”
Section: Mbp Genotypesmentioning
confidence: 87%
See 3 more Smart Citations
“…encoded in exon 1 ofihe MBP gene; 64 were homozygous Ibr Ihc GGC allele (71 9"/,,); 21 were heterozygous for the GAC allcle (23-5%); and four were homozygous for the GAC allele (4 5%), respectively (Table I), This gives a frequency ofthe GAC allele of 0-16. which is nol significantly differenl from that of healthy Danish controls (0-13) (/*-0-65) [20] (Fig. 3).…”
Section: Mbp Genotypesmentioning
confidence: 87%
“…The variant allele causes an aminoacid substitution in exon I at codon 54 in the collagen-!ikc domain iti the MBP gene (GGC (glycine) to GAC (aspartic acid)). This mutatioti is remarkably frequent in both Caucasians and Eskimos, wilh an estimated allele frequeney of 013 in bolh populaiions [20,21], However, this mutation alone cannot account for all cases of MBP deficiency, because MBP deficiency was also seen in some individuals found with Ihe normal genotype (GGC). Another mutation associated with low MBP plasma concentrations at eodon57inexon 1 in the M BP gene ha.s been found in bolh Wesi and East Afriea.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a Australian study involving 236 healthy blood donors, 30% were found to be heterozygous for structural gene mutations, and an additional 8% were homozygous or had double mutations of the structural genes (39). The codon 54 variant has an observed frequency of 42%-46% in South American Chiriguanos and Mapuches (40); in Danish, Midwestern American, and Greenland Eskimo population groups, the frequency is 11%-13% (41,42).…”
Section: Discussionmentioning
confidence: 99%